Straits Settlements Blue Book (imports/exports) 1914 vol.62 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports during the year 1914';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other Countries in 1913 and 1914'.